"Space, culture and power" - "Weyland, Petra (ed.)" (London, 1997)
Large cities in both the North and the South are caught in the contradictory logics of globalization and localization. This work looks at how ethnic minorities, tribal groupings and marginalized subcultures in urban areas appropriate contemporary discourses - of consumerism, Islam, human rights - to voice new cultural alternatives. Through a variety of cities, including Beirut, Berlin, Cairo, Istanbul, Manila and Singapore, it explores how social and cultural boundaries are renegotiated as new social networks of global trade and finance create new opportunity spaces. It looks at the political agendas and strategies of groups who mobilize to seize upon these openings, and aims to show how the global is translated by different urban groups into practices which transform physical, social and cultural spaces.
Keywords: Metropolitan